The Essential of Planning Programming Budgeting Systems and Their Applicability in Public Sector: A Comparative Analysis of PPBS and TBS in Public Sector Budgeting (Journal of Advances and Scholarly Researches in Allied Education, 2017)
There are varying views throughout on the necessity for a public budget since timeimmemorial. The main reason for the early use was the desire to limit governmental expenditure and taxesbefore the 20th century. In the mid-20th century, socio-economic conditions and thus budgetingchanged greatly globally. Keynesian thought has caused a large number of economists not only to seethe government budget as a legislative instrument, but also as an instrument of public sector politics,economy, accounting and administration. Since then, a variety of disciplines have studied the budget.This article examines the question of PPBS and its applicable public sector budgeting and budgetingmethods. Comparisons have shown that although TBS is extensively utilized within the public sector,PPBS is nevertheless the most functional technology for budgeting applications.